Warfare to Welfare: How Social Identity Supports the Political Business of the Former Free Aceh Movement - Hajad, Vellayati; Aprita Sari, Cut Maya (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This study critically examines how former members of the Free Aceh Movement (GAM) transformed their collective social identity into political and economic capital in post-conflict Aceh. Drawing on social identity theory (SIT) and sociocognitive processes, it challenges prevailing reintegration narratives that emphasise disassociation from militant pasts. Instead, it finds that former GAM members deliberately retained and mobilised their rebel identity to gain legitimacy, patronage, and access to state resources. The study identifies three internal identity trajectories: the “ruling group", which converted its identity into formal political power; the “contractor group”, which leveraged political ties to access state-funded economic projects; and the “common society group”, which remained socially and economically marginalised. This stratification reveals that identity transformation does not uniformly lead to welfare gains. While existing studies often frame ex-combatant reintegration as a linear transition toward civilian life, this study argues that identity retention—rather than abandonment—can be a strategic pathway to upward mobility. However, this process is uneven. Enabling factors, such as provisions within the Helsinki Memorandum of Understanding (MoU), the institutional structure of the Aceh Transition Committee (KPA), and the symbolic value of the GAM identity, supported elite access. In contrast, constraining factors, including limited economic diversification, dependency on political patronage, and exclusionary practices, prevented broader benefit-sharing among lower-tier members. By exposing the unequal outcomes of identity-based transformation, this study critiques assumptions of uniform reintegration success and offers a differentiated lens for understanding post-conflict access and inequality.